1999
DOI: 10.1006/inco.1998.2778
|View full text |Cite
|
Sign up to set email alerts
|

A Partial Order Approach to Branching Time Logic Model Checking

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 2 publications
1
29
0
Order By: Relevance
“…Condition D1' is very similar to condition C1 [5], which is common in the context of ample sets. However, C1 requires that action a is globally independent of each of the actions a 1 , .…”
Section: Strengthening Condition D1mentioning
confidence: 78%
See 1 more Smart Citation
“…Condition D1' is very similar to condition C1 [5], which is common in the context of ample sets. However, C1 requires that action a is globally independent of each of the actions a 1 , .…”
Section: Strengthening Condition D1mentioning
confidence: 78%
“…When applying stubborn sets in that context, stronger conditions are required to preserve the branching structure that CTL −X reasons about. Namely, the original LSTS must be deterministic and one more condition needs to be added [5]:…”
Section: Deterministic Lstss and Ctl −X Model Checkingmentioning
confidence: 99%
“…The heuristic function takes structural properties of the state space as well as properties of the requirements specification into account. (1) procedure GSEA(s) (2) Closed ← ∅; Open ← {s} (3) while not Open.empty() do (4) u ← Open.extract(); Closed.insert(u); (5) if goal(u) then return solution; (6) for each a ∈ enabledT do (7) v ← τ (u, a); process (v); (8) if reopenOK(v) then Closed .delete(v); (9) if v ∈ Closed and v ∈ Open then Open.insert(v);…”
Section: Directed Model Checkingmentioning
confidence: 99%
“…The BIR fragment in figure 5 illustrates how the compound test on lines [18][19][20] of figure 2 is translated to a series of guarded transformations in BIR and how a field assignment is expressed directly.…”
Section: Basic Transformations and Visibilitymentioning
confidence: 99%
“…An invisible action is however not independent with other non-deterministic choices of the same thread, and for this reason we need to preserve the internal branching structure of a thread when defining the transition system. It can been shown that treating invisible transformations by disallowing interleavings with other threads generates a labeled transition system that is branching bisimilar [20] to the fully interleaved one. Assuming that the invisible labeling of transformations preserves state stuttering i.e., two states connected by an invisible transition will satisfy the same set of predicates, this semantics strongly preserves the truth value of formulas written in the next-free CTL* temporal logic [44].…”
Section: Transition Systemmentioning
confidence: 99%